2021
DOI: 10.1080/14686996.2021.1907222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and fluid permeability of gyroid and diamond lattice structures for intervertebral devices: functional requirements and comparative analysis

Abstract: Current intervertebral fusion devices present multiple complication risks such as a lack of fixation, device migration and subsidence. An emerging solution to these problems is the use of additively manufactured lattice structures that are mechanically compliant and permeable to fluids, thus promoting osseointegration and reducing complication risks. Strut-based diamond and sheet-based gyroid lattice configurations having a pore diameter of 750 µm and levels of porosity of 60, 70 and 80% are designed and manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 64 publications
0
24
0
1
Order By: Relevance
“…Recently, Kelly et al demonstrated a non-linear relationship between osseointegration shear strength and titanium alloy gyroid implants with varied porosity in an ovine cortical model, concluding the porosity and thus surface area of the implant are important factors for stabilization. These findings are supported by experiments showing that the gyroid lattice is suited to biomorphic scaffold design in tissue engineering and has a superior ability to promote cell differentiation and proliferation when compared to other traditional arrangements [ 37 , 38 ]. Additionally, the corrosion of 80% gyroid lattices have recently been explored with Qin et al demonstrating that Zn-0.7Li gyroids displayed lower weight loss than their bulk equivalent [ 39 ], whist another study showed that gyroid lattices exhibit higher polarisation resistance compared to 80% primitive and diamond lattices when exposed to a potassium hydroxide solution, suggesting gyroids have the strongest resistance to corrosion within the TPMS category [ 40 ].…”
Section: Introductionmentioning
confidence: 74%
“…Recently, Kelly et al demonstrated a non-linear relationship between osseointegration shear strength and titanium alloy gyroid implants with varied porosity in an ovine cortical model, concluding the porosity and thus surface area of the implant are important factors for stabilization. These findings are supported by experiments showing that the gyroid lattice is suited to biomorphic scaffold design in tissue engineering and has a superior ability to promote cell differentiation and proliferation when compared to other traditional arrangements [ 37 , 38 ]. Additionally, the corrosion of 80% gyroid lattices have recently been explored with Qin et al demonstrating that Zn-0.7Li gyroids displayed lower weight loss than their bulk equivalent [ 39 ], whist another study showed that gyroid lattices exhibit higher polarisation resistance compared to 80% primitive and diamond lattices when exposed to a potassium hydroxide solution, suggesting gyroids have the strongest resistance to corrosion within the TPMS category [ 40 ].…”
Section: Introductionmentioning
confidence: 74%
“…The first one defines the maximum 3D space dimension that can be accommodated within the smallest pore structure within the porous material as the pore size. Then it defines the maximum 2D plane dimension that interconnects the pore structure inside the porous material with other adjacent pore structures as the pore throat size, as shown in Figure 2A ( Afshar et al, 2016 ; Jette et al, 2018 ; Ambu and Morabito, 2019 ; Wang et al, 2020 ; Lehder et al, 2021 ; Timercan et al, 2021 ). The second one defines the maximum 2D plane dimension of the pore within the porous material that interconnects with other adjacent pore structures as the pore diameter.…”
Section: Definition Of Pore Structure Dimensionmentioning
confidence: 99%
“…This automatic measurement technique works with spheres of different diameters by moving and filling the space structure until the boundary conditions are reached after the spheres form a tangent to the structure. Then the diameters of the spheres are included in the statistics and counted, eventually resulting in aperture diameter distribution curves related to the diameter and number of spheres, as shown in Figure 3F ( Jones et al, 2007 ; Taniguchi et al, 2016 ; Timercan et al, 2021 ). In this measurement, the definition of pore size and pore throat diameter is ignored.…”
Section: Measurement Of Pore Structure Dimensionsmentioning
confidence: 99%
“…This limits their applicability when trying to understand trabecular bone mechanics, and also could limit their application in designing biomimetic structures (Kang et al, 2020) produced through additive manufacturing e.g. for applications that include bone substitutes, scaffolds (Rammohan et al, 2015;Rammohan and Tan, 2016;Timercan et al, 2021;Yánez et al, 2016), and porous implants (Deering et al, 2021).…”
Section: Introductionmentioning
confidence: 99%